Comparative Physiological and Transcriptomic Analyses Reveal Mechanisms of Exogenous Spermidine-Induced Tolerance to Low-Iron Stress in Solanum lycopersicum L - Yu Shi; Yihong Zhao; Qi Yao; Feng Liu; Xiumin Li; Xiu Jin; Yi Zhang; Golam Jalal Ahammed (Antioxidants, 2022)
Iron (Fe) deficiency in plants is a major problem in agriculture. Therefore, we investigated both the physiological features and molecular mechanisms of plants’ response to low-Fe (LF) stress along with the mitigation of LF with exogenous spermidine (Spd) in tomato plants. The results showed that exogenous Spd foliar application relieved the suppressing effect of LF stress on tomato plants by regulating the photosynthetic efficiency, chlorophyll metabolism, antioxidant levels, organic acid secretion, polyamine metabolism and osmoregulatory systems. Analysis of transcriptomic sequencing results revealed that the differentially expressed genes of iron-deficiency stress were mainly enriched in the pathways of phytohormone signaling, starch and sucrose metabolism and phenyl propane biosynthesis in both leaves and roots. Moreover, Spd-induced promotion of growth under LF stress was associated with upregulation in the expression of some transcription factors that are related to growth hormone response in leaves (GH3, SAUR, ARF) and ethylene-related signaling factors in roots (ERF1, ERF2). We propose that traits associated with changes in low-iron-tolerance genes can potentially be used to improve tomato production. The study provides a theoretical basis for dealing with the iron deficiency issue to develop efficient nutrient management strategies in protected tomato cultivation.